2021
DOI: 10.3389/fcvm.2021.686200
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Mediates Thrombin-Induced Vascular Smooth Muscle Cell Migration

Abstract: Vascular smooth muscle cell (VSMC) migration is an important step in the progression and development of vulnerable plaques. Thrombin is involved in both physiological and pathological processes of atherosclerosis. Therefore, the elucidation of the mechanisms underlying thrombin-induced VSMC migration is essential for devising effective treatments aimed at the prevention of plaque instability. In this study, we found that thrombin activated MAPK signaling pathways and increased the expression of galectin-3, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…LGALS3 is related to the MAPK signaling pathway (32), which corresponded with our RNA-seq sequencing analysis results, further indicating that Telotristat Etiprat could affect the MAPK signaling pathway by binding to LGALS3.…”
Section: Discussionsupporting
confidence: 84%
“…LGALS3 is related to the MAPK signaling pathway (32), which corresponded with our RNA-seq sequencing analysis results, further indicating that Telotristat Etiprat could affect the MAPK signaling pathway by binding to LGALS3.…”
Section: Discussionsupporting
confidence: 84%
“…LGALS-3 inhibition increases CNN1 and ACTA2 gene expression in human pulmonary arterial SMCs under hypoxic conditions [ 100 ]. LGALS-3 is considered a predictive marker for the development and progression of CVDs [ 101 ], including atherosclerosis [ 102 ]. In addition to promoting SMC migration and phenotypic switching to the synthetic type through the Wnt/β-catenin signalling pathway [ 103 ], LGALS-3 is actually intimately involved in acute inflammation and in its chronicization [ 104 , 105 , 106 ].…”
Section: Resultsmentioning
confidence: 99%
“…The basement membrane provides cellular cues, enhances endothelial cell adhesion, and acts as a physical barrier for transmigration of vascular smooth muscle cells to vessel lumen in order to prevent intimal hyperplasia and atherogenesis. [19][20][21] Due to the limited mechanical properties of acellular matrix scaffolds, the chemical crosslinking method was adopted in the present study to improve the mechanical strength of the scaffolds. The crosslink often results in increased collagen stiffness, reduced elasticity, and compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Scanning electron microscopy analysis revealed that the basement membrane appeared intact and smooth without underlying porous fibrous network exposure. The basement membrane provides cellular cues, enhances endothelial cell adhesion, and acts as a physical barrier for transmigration of vascular smooth muscle cells to vessel lumen in order to prevent intimal hyperplasia and atherogenesis 19–21 …”
Section: Discussionmentioning
confidence: 99%